Pennū gannū paṭṭina prajākavi Pāṇigrāhi - Rāmābu, Ē (Viplava Racayitala Saṅghaṃ, Vijayanagaraṃ Yūniṭ ; kāpīlaku, "Srjana" Māsapatrika, 1982)
Life and works of Subbarao Panigrahi, 1932 or 3-1969, revolutionary Telugu poet; includes selected songs, without musical notation.